A desconsideração da personalidade jurídica - Arai, Cíntia Lumy (2014)
The purpose of the present study is to discuss the application of the disregard doctrine, empathizing its characteristics and the most relevant and current issues that are being discussed by the Brazilian legal system. The financial liability is directly related to the study of the disregard doctrine, therefore it is necessary to address the issue, primarily on the liability of a shareholder. The reverse disregard doctrine, a widely accepted practice by the courts, is addressed by confronting updated judgments and conclusions of many legal scholars. The design of the “New Code of Civil Procedure” is an important issue of this study, because there is an undeniable necessity to create specific laws concerning the disregard doctrine due to the success achieved with the application of this institute